PENGARUH PENAMBAHAN SARI BUAH SIRSAK (Annona muricata L.) TERHADAP KARAKTERISTIK YOGURT EDAMAME (Glycine max L.) - Kartika, Dina Puti; Permana, I Dewa Gde Mayun; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 4 (2019): Jurnal ITEPADO - 10.24843/itepa.2019.v08.i04.p04, 2019)
This study aims to determine the effect of soursop juice on the characteristics of edamame yogurt and to determine the optimal concentration of soursop juice to produce edamame yogurt with the best characteristics. This study used a Randomized Block Design (RBD) with the treatment of soursop fruit juice concentration consisting of 5 levels, namely 0%, 5%, 10%, 15% and 20%. Each treatment was repeated 3 times, resulted in 15 experimental units. The data were analyzed by the Analysis of Variance (ANOVA) and if the treatment significantly affected the variables, the Duncan Multiple Range Test (DMRT) was performed. The results showed that the concentration of soursop juice significantly affected total LAB, total acid, pH, antioxidant activity, viscosity, sensory hedonic test on texture and sensory scoring test on texture and taste. The edamame yogurt with 15% soursop juice had the best characteristics with the following characteristics: total LAB 1.01 x 10 11 CFU/ml, total acid 0.86%, viscosity 310 cP, antioxidant activity 35.47%, pH 3.72 and the sensory properties of neutral scents, neutral appearance, a rather thick texture, a rather like taste, a slightly sour taste and a rather like overall reception. Keywords : edamame yogurt, soursop juice, antioxidant activity